Pelatihan Aplikasi SAP2000 Untuk Meningkatkan Kemampuan Dalam Penyelesaian Problem Mekanika Teknik Bagi Siswa SMKN 2 Surabaya - Imaduddin, Muhammad; Sabariman, Bambang; Aritonang, Nurhayati; Wardhono, Arie; Rahmadyanti, Erina (LPPM Universitas Bhayangkara Surabaya, 2024)
In accordance with Presidential Instruction (Inpres) Number 9 of 2016 concerning the Revitalization of Vocational High Schools (SMK) in the context of Improving the Quality and Competitiveness of Indonesian Human Resources (HR), it is necessary to compile a map of labor needs for SMK graduates according to their respective duties, functions, and authorities based on the road map for vocational development. One of the targeted developments is the skill of using computer applications in accordance with its basic competencies. Currently, engineering mechanics lessons at SMKN 2 Surabaya are only given theoretically. The use of computer applications to help solve existing problems has not been implemented. Even though work challenges today really require these skills to solve more complicated problems, more quantities, and faster solutions. Based on the above, this PKM activity aims to improve students' ability to use SAP2000 applications to solve engineering mechanics problems. The training provided includes an introduction to the basic use of SAP2000 including the use of the menus in it. Followed by the practice of working on example problems along with discussing their theoretical validation. After that, exercises for more complicated problems are given which end with giving quizzes to further motivate students. From the post-test results given at the end of the training, the results showed that 85.58% of trainees could understand the training material well. This shows that this training is very effective in improving students' abilities which is expected to bring benefits as a provision to face work challenges after graduation.